Revesz syndrome - Issaho,Dayane Cristine (2015)
Revesz syndrome is a rare variant of dyskeratosis congenita and is characterized by bilateral exudative retinopathy, alterations in the anterior ocular segment, intrauterine growth retardation, fine sparse hair, reticulate skin pigmentation, bone marrow failure, cerebral calcification, cerebellar hypoplasia and psychomotor retardation. Few patients with this syndrome have been reported, and significant clinical variations exist among patients. This report describes the first Brazilian case of Revesz syndrome and its ocular and clinical features.